Atheism, Atoms, and the Activity of God: Science and Religion in Early Boyle Lectures, 1692–1707 - Lim, Paul Chang-Ha (Zygon, 2021)
The last-half of seventeenth-century England witnessed an increasing number of works published questioning the traditional notions of God's work of creation and providence. Ascribing agency to matter, motion, chance, and fortune, thinkers ranging from Hobbes, Spinoza, modern-Epicureans, and other presented a challenge to the Anglican defenders of social and ecclesiastical order. By examining the genesis of the Boyle Lectures that began in 1692 with a bequest from Robert Boyle, we can see that while the Lecturers—three of whom will be examined in detail (Richard Bentley, John Harris, and William Whiston)—assiduously defended classical notions of the God-world relationship, they did so without a great sense of panic or pessimism. This transitional period in the mode of conflict or concord between religion and science sheds interesting lights on matters such as argument from design, biogenesis without purposive, personal agents, and scriptural exegesis and scientific inquiries.